Planning a clinical trial programme for direct-acting antivirals for chronic viral hepatitis C - A. I. Gubenko; D. V. Goryachev; A. I. Muravieva; G. V. Shukshina (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Scientific relevance. Direct-acting antivirals have significantly improved the effectiveness of treatment for hepatitis C. However, Russia and the Eurasian Economic Union lack recommendations for the clinical development of medicinal products from this pharmacotherapeutic group.Aim. The study aimed to analyse the requirements and recommendations for planning safety and efficacy clinical trials of direct-acting antivirals for chronic viral hepatitis C, outlined in the regulatory documents of the European Union and the United States.Discussion. Upon analysing the requirements and recommendations, the authors explained the reasons behind choosing the target population and the design for the efficacy and confirmatory studies. The article covers the clinical development of direct-acting antivirals in special populations, including patients with hepatitis C and HIV co-infection, a liver transplant, and prior treatment experience. According to the authors, patients who achieved a sustained virological response should be followed up for a full year after the end of treatment in order to confirm the durability of their response. A dose-finding study should first identify a suitable dose range for monotherapy and, subsequently, for combined therapy. Current treatment regimens should be optimised, and studies should be conducted to reduce treatment duration.Conclusions. The authors outlined the main approaches and a methodology for clinical trial programmes that should take into account the degree of correlation between the efficacy of direct-acting antivirals and the genotype/subtype of hepatitis C virus.